PENGEMBANGAN UKM MELALUI PELATIHAN DAN PENDAMPINGAN MANAJEMEN USAHA DI SENTRA SEPATU CIBADUYUT - Siti Patimah (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
Cibaduyut region is an area artisans developed as centers of production of shoes and shoe shopping in one of Bandung. But in recent years Cibaduyut shoe manufacturing business began to fall. To overcome the problems faced Cibaduyutshoe craftsmen, the effort is to implement a management training activities. The activities are the Actual Problem Solving, target audiences, including the method of approach to a lecture, discussion and simulation as well as action plansto be implemented. The result of this activity is that the participants are so enthusiastic to participate in a mentoring training. Of business management training delivered, the participants do not understand the preparation related to human resources management, Feasibility Studies Business and Accounting simple. But with the training and mentoring, the craftsmen began to understand the importance of keeping preparation simple addition to determine the profit in business is alsoimportant for business continuity in the future.